DI-028 Reasons for changing treatment to oral agents in multiple sclerosis. (25th February 2017) - Molina, M; Rodriguez, E; Gonzalez, A; Gonzalez, L; Moreno, F; Jimenez, I; Freire, M; Herrero, A
Abstract : Background: People with multiple sclerosis (MS) now have oral drugs to choose from to treat the relapsing form of the disease. Aubagio (teriflunomide) is an oral compound that inhibits the function of specific immune cells that have been implicated in MS. It has been approved for patients with relapsing forms of MS. Purpose: The aim of this study was to analyse changes in relapsing forms of MS treatment from injectable drugs to the oral drug teriflunomide. Material and methods: This was an observational retrospective study. Data were obtained from 20 patients with MS treated with teriflunomide from January 2016 to June 2016. We reviewed the medical history to confirm the reason for changing to the new drug: lack of efficacy or adverse effects with the previous therapy, patient preferences for oral drug versus injectable drugs and risk of progressive multifocal leukoencephalopathy from natalizumab. Data collected were : age, gender, previous treatment and reasons for changing. Results: We included 20 patients that started treatment with teriflunomide. 57% were women. Median age was 49±10 (SD) years. Previous therapies and number of patients that received it: Avonex 1; Betaferon 5; Copaxone 2; Tysabri 3; Rebif 1; Rebif and Tysabri 2; Tysabri and Betaferon 1; Betaferon and copaxone 1; Betaferon and avonex 1; Tysabri, Betaferon and Rebif 1; and azathioprine, Betaferon, Copaxone and Tysabri 1. 1 patient received therapy from a clinical trial. Reasons for changing therapy : lack of efficacy 10 (50%), risk of progressive multifocal leukoencephalopathy from natalizumab 4 (20%), patient preferences for oral drug versus injectable drugs 2 (10%), adverse effects with the previous therapy 1 (5%) and unknown 3. Conclusion: The main reason for changing MS treatment was lack of efficacy of previous therapies followed by risk of progressive multifocal leukoencephalopathy from natalizumab. New oral agents are easier to administer for patients; this is an important advantage for these compounds. Emerging oral treatments are ushering in a new era in the treatment of MS, providing not only new treatment options but also new challenges. No conflict of interest